Continuity and change in the realms of Islam studies in honour of Professor Urbain Vermeulen - Vermeulen, Urbain 1940-; Hulster, K. d' (Kristof d'); Steenbergen, J. van (Orientalia Lovaniensia analecta, 2008)
This liber amicorum for Urbain Vermeulen contains forty studies on a wide variety of topics, written by friends, colleagues and former students. It reflects the international appreciation for this Belgian orientalist and the many realms of Islamic studies he engaged in. The general merit of the volume is the interaction between the many traditions and changes that continue to make up the world of Islam, including contributions on the history, art history, archaeology, religion, linguistics and literature of the premodern and modern Islamic world. Individual topics deal with Fatimid, Ayyubid and Mamluk studies in many different forms and shapes, with the intricacies of Arabic, Turkish and Persian historiography, poetry, popular epic and lexicography, with libraries in the East and Far East, with subtle issues of theology, philosophy and anthropology, and with representations of the Orient from the crusading era until today